Pemberdayaan Madrasah Melalui Implementasi Metode UMMI Untuk Peningkatan Pembelajaran Al-Qur’an: Participatory Action Research di MI Maslakul Huda Lamongan - Zainul Fuad; Nafilatur Rohmah (MADINAH, 2025)
This research aims to empower madrasah communities in implementing better methods of learning the Quran. The problem faced is that MI Maslakul Huda has not been able to optimally implement the 10 pillars of Ummi quality, despite joining since 2018. This research uses the Participatory Action Research (PAR) approach, which involves all parties at the madrasah as research partners, not just research objects. The research was conducted with the involvement of madrasah principals, teachers, coordinators, committees, and students' parents. Data was collected thru participant observation, group discussions, in-depth interviews, and documentation. The PAR process is conducted in 4 cycles: jointly identifying the problem, reflecting on the causes, taking corrective action, and evaluating the results. The results show an improvement in the implementation of the 10 pillars of Ummi quality from an average of 71.5 (sufficient) to 84.8 (good). The highest increases were in the learning time aspect (+21 points), coordinator ability (+20 points), and target clarity (+20 points). The research successfully fostered a sense of shared ownership and commitment to sustain the program. This empowerment model can be applied in other madrasas with adjustments to local conditions.